2019
DOI: 10.18535/ijsrm/v7i9.mp04
|View full text |Cite
|
Sign up to set email alerts
|

Residual ridge resorption, the effect on prosthodontics management of edentulous patient: an article review

Abstract: Bone resorption is a chronic, progressive disease and irreversible process that occurs in all patients and can be classified into six different types. There are some of etiological factors that may cause resorbed ridge such as anatomical, prosthodontics, metabolic and systemic factors. The present article, were reviewed the literature concerning on possible mechanism, diagnosis, etiological factors and how to manage and prevent of resorbed ridge for edentulous patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…As CBCT provides volumetric information, it conveys medically important information about the patients’ anatomy and the possible bony changes 38 . Furthermore, studies use CBCT as a method to evaluate bone changes because it has shown an absence of distortion and overlapping and the dimensions it presents are compatible with the actual size 39 . Also, when evaluating edentulous sites, CBCT can be used for precise identification and reliable assessment of bone changes 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As CBCT provides volumetric information, it conveys medically important information about the patients’ anatomy and the possible bony changes 38 . Furthermore, studies use CBCT as a method to evaluate bone changes because it has shown an absence of distortion and overlapping and the dimensions it presents are compatible with the actual size 39 . Also, when evaluating edentulous sites, CBCT can be used for precise identification and reliable assessment of bone changes 40 .…”
Section: Discussionmentioning
confidence: 99%
“…38 Furthermore, studies use CBCT as a method to evaluate bone changes because it has shown an absence of distortion and overlapping and the dimensions it presents are compatible with the actual size. 39 Also, when evaluating edentulous sites, CBCT can be used for precise identification and reliable assessment of bone changes. 40 CBCT was used in a previous study 30 for monitoring ridge base relation and was used in other studies to evaluate alveolar bone height and its loss as it provides an accurate 3D image, with a minimal dose of radiation compared to conventional CT system.…”
Section: Discussionmentioning
confidence: 99%
“…The fabrication of complete dentures for edentulous patients with a high degree of residual ridge absorption can be clinically difficult. There is an increasing possibility of encountering such challenging cases in daily dental practice due to our unprecedented superaging society [6,7].…”
Section: Introductionmentioning
confidence: 99%